Rancangan Sistem Informasi Penjualan Tas Berbasis Web Pada Ã¢â‚¬Å“GIKITAÃ¢â‚¬Â Online Shop - Setiawan, Joko (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2018)
Gikita Online Shop is an online store that sells bag products located in Batam. During this Core Online Shop has been promoting its business using social media like Facebook, Line, Blackberry messenger, Whatsapp and Instagram. The purpose of this research is to design a web-based bag sales information system to facilitate the purchase of goods without having to check social media. Applications designed in the manufacture of bag sale websites using CMS Opencart. The results of the manufacture of this bag sale website is expected to help facilitate in managing the goods to no longer use the manual way of inputting data items and can minimize the occurrence of data errors by using the web.